(untitled) (Research, Society and Development, 2023)
The large consumption of açaí in the Amazon region drives the emergence of a class of workers specialized in managing the fruit. The case report presented here analyzes the occupational hazards to which workers involved in the açaí production chain are exposed, with emphasis on the ergonomic risk associated with carrying loads of açaí berry. The study aims to do an ergonomic evaluation of the work activity and trace the epidemiological and clinical relationship of the inguinal hernia with the profile of the patient treated. In a medical consultation performed at the Reference Center for Worker’s Health, located in Belém, Pará, an occupational anamnesis and physical examination investigated the case of a male patient, 50 years old, merchant and porter of açaí berry with a lump painless in the left inguinal region arising on exertion. The condition of inguinal hernia presented was characterized as a pathological repercussion associated with the workday in which there is the daily and repetitive carrying of heavy loads of açaí, which possibly caused the increase in intra-abdominal pressure and the weakening of the transversalis fascia. The case made it possible to define the existence of ergonomic risk factors common to workers in the açaí sales business, contributing to the development of management strategies for the health of these workers and helps in understanding the relationship between work and the health-disease process.